EFISIENSI MANAJEMEN PEMESANAN MELALUI APLIKASI PENCATATAN DIGITAL PADA RUMAH JAHIT IBU BYPASS KECAMATAN KOTO TANGAH KOTA PADANG - Komalasari, Sanda Patrisia; Primadini, Nurul Ulfa; Wisti, Mutia Pramodya; Fitriyani, Widya Nurul; Putri, Zelvoni Yunitra; Sefnita, Sefnita; Utami, Widi Mega (LPPM Universitas Andalas, 2024)
The purpose of this activity is to assist Rumah Jahit Ibu, located in Bypass, Padang City, in overcoming challenges related to product order recording, which is currently done manually using a ledger. This manual recording method leads to disorganization, delays, and potential errors in managing order data. To address these issues, the service team designed and developed a digital recording application using Microsoft Access. The process began with analyzing Rumah Jahit Ibu's needs, followed by designing an appropriate application, development, and user training to ensure effective use of the application. The outcome of this activity is an order recording application that enables Rumah Jahit Ibu to record, manage, and monitor orders in a more structured and accurate manner. The application provides features that facilitate transaction recording, data processing, and receipt identification for each customer. With this application, the recording process becomes faster, errors in recording can be minimized, and order data can be accessed and managed more effectively. The conclusion of this activity indicates that the implementation of the Microsoft Access-based application significantly improves efficiency and accuracy in order management at Rumah Jahit Ibu. The use of this application not only enhances the recording system but also provides ease in monitoring and identifying orders, ultimately improving customer satisfaction and overall business performance